Disability's Digital Frictions: Activism, Technology and Politics - Ellis, Katie; Goggin, G.; Kent, Michael (2015)
This paper argues that disability activism and politics can be seen as paradigmatic for the wider debates on the philosophies, forms, and formats embedded in technologies. Firstly, the paper discusses disability activism movements that use digital technology to intervene into digital technology, especially in the social media area. In both cases, activists seek to use the platforms themselves to argue for, and obtain, greater accessibility, customisability, and configurability, of the platform for users with disabilities. Yet there is a clear clash between philosophies embedded within these social media platforms, and the aspirations and values of many of the activist strands of disability. Secondly, the paper explores the use of digital technologies by disability activism movements in relation to welfare and work reforms—notably the UK struggles in the 2010–2014 periods. Here disability activists have made extensive use of digital media technologies, and we discuss their innovations, and the lessons they offer.